Green Banking and Liquidity: Strategies for Optimising Islamic Bank Profitability - Astuti, Retno Puji; Nurhasanah, Nurhasanah; Chairunisa, Mariyam; Almunawar, Safira; Melzatia, Shinta (Inisiatif Masyarakat Jurnal Indonesia (IMAJI), 2024)
Environmental challenges such as climate change and natural disasters are on the rise. One of the factors contributing to this problem is environmentally unfriendly banking. Therefore, green banking is a concept that focuses on reducing carbon emissions both inside and outside the bank. The purpose of this study was to analyse the effect of green banking and liquidity on the profitability of Islamic commercial banks. The population of this study is the Islamic banks registered with the Financial Services Authority (OJK) for the period 2018-2022. The sampling method used was purposive sampling, with a total sample of 11 Islamic commercial banks. The data analysis technique used in this study is multivariate regression analysis using Eviews 12 statistical tool. The results of this study indicate that green banking has a negative and insignificant effect on the profitability of Islamic commercial banks. And liquidity has no effect on the profitability of Islamic commercial banks.